2021
DOI: 10.1177/14624745211018760
|View full text |Cite
|
Sign up to set email alerts
|

“I have to be a man for my son”: The narrative uses of fatherhood in prison

Abstract: Research on incarcerated fathers tends to accentuate the harmful familial consequences of parental incarceration and discuss how having children might prompt incarcerated fathers to desist from crime. Less attention has focused on how narratives of fatherhood shape the day-to-day dynamics of incarceration. Drawing on 93 qualitative interviews with incarcerated fathers in Western Canada, we focus specifically on our participants’ parenting narratives. Such narratives are significant interventions in the world, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 58 publications
0
7
0
Order By: Relevance
“…At the same time, in the construction of artistic narratives, men deprived of liberty also discussed how they contemplated possible postprison futures and possibilities for change, linking the future with new ways of being a man, especially through new forms of fatherhood. The important role that fatherhood plays in the construction of prison masculinities has been well documented in the literature (Sandberg et al, 2022; Schultz et al, 2023); however, in Chile, it is still relatively underresearched. As José Olavarría states when analyzing paternity in popular-sector men: “Paternity is lived in this manner, as the possibility of change that gives meaning to personal life and implies responsibilities and challenges that must be confronted: co-habitation, maybe getting married, working.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, in the construction of artistic narratives, men deprived of liberty also discussed how they contemplated possible postprison futures and possibilities for change, linking the future with new ways of being a man, especially through new forms of fatherhood. The important role that fatherhood plays in the construction of prison masculinities has been well documented in the literature (Sandberg et al, 2022; Schultz et al, 2023); however, in Chile, it is still relatively underresearched. As José Olavarría states when analyzing paternity in popular-sector men: “Paternity is lived in this manner, as the possibility of change that gives meaning to personal life and implies responsibilities and challenges that must be confronted: co-habitation, maybe getting married, working.…”
Section: Resultsmentioning
confidence: 99%
“…However, in carceral contexts, this is given an additional layer of complexity, as strong homosocial and homoerotic bonds are created, ones that do not necessarily threaten the heteronormative patterns followed outside of prison and in their families of origin (Crewe, 2014;Ortiz González et al, 2019;Parrini, 2007). Finally, as many studies have shown, prison masculinities are also often constructed with regard to the past-for example, with regard to past gender and sexual violence (Franzén & Gottzén, 2022)-as well as the future, as being a "good father" to their children often permits freedom-deprived men to envision better, postprison futures (Sandberg et al, 2022;Schultz et al, 2023). Additionally, as Evans and Wallace (2008) have shown, different conceptualizations of masculinities have a strong effect on inmates' possibilities of identity formation, particularly with regard to continuity and change of certain behaviors and attitudes and understanding their lives in and outside of prison.…”
Section: Allow Us To Recognize Structuralmentioning
confidence: 99%
“…We speculate this variable may be spurious, generally reflecting that our study and control groups averaged 34 years of age, slightly higher than the Canadian average of 31 years for men's first marriage (Milan, 2013). Relationships played no role in radicalization narratives or perspectives in these specific data (but see Schultz et al, 2021b).…”
Section: Samplementioning
confidence: 96%
“…On the one hand, the prison code includes prescriptions that exert a regulatory force over individuals, steering behavior in prescribed directions to varying degrees depending on situational specifics. On the other hand, incarcerated individuals can invoke the code in a flexible, pragmatic, or contextualized manner to justify and rationalize different behaviors (Jimerson & Oware, 2006; Schultz et al., 2021b; Wieder, 1974). Consequently, the prison code can be both a cause of conduct and what Mills (1940) referred to as a “vocabulary of motive” that incarcerated individuals use strategically to account for their actions.…”
Section: Context and Literature Reviewmentioning
confidence: 99%
“…An additional challenge for parents in general is that imprisonment interrupts and makes parents "miss out" on their relationships with children (Chen 2009;Collica 2010;Foster 2012). Both men and women indicate that being separated from children is an especially painful aspect of incarceration (Arditti and Few 2008;Loper et al 2009;Schultz, Bucerius, and Haggerty 2021).…”
Section: Programmingmentioning
confidence: 99%